2019
DOI: 10.1016/j.imr.2019.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Evidence, safety and recommendations for when to use acupuncture for treating cancer related symptoms: a narrative review

Abstract: Background Recently research on acupuncture for cancer related symptoms has significantly increased. To what extent have medical professionals recommended to use acupuncture in light of that evidence? Methods Evidence of effectiveness and safety was found by searching Pubmed for reviews to identify for what conditions and general results. Publications that recommend acupuncture in oncology were searched in the database of an ongoing general search for publications that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 72 publications
1
30
0
Order By: Relevance
“…Modern technology has suggested that acupuncture can modulate neurological processes within the central nervous system (30), stimulate the autonomic nervous system and increase peripheral blood flow (16), which generally benefits patients undergoing radiation despite mechanism remains partly understood (24,31). Since acupuncture theories and needling instruments gradually developed, a growing number of acupuncture therapies have emerged in the meantime, making clinical application a manifold yet tough decision as it remains inconclusive which treatment can reap the greatest benefits.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Modern technology has suggested that acupuncture can modulate neurological processes within the central nervous system (30), stimulate the autonomic nervous system and increase peripheral blood flow (16), which generally benefits patients undergoing radiation despite mechanism remains partly understood (24,31). Since acupuncture theories and needling instruments gradually developed, a growing number of acupuncture therapies have emerged in the meantime, making clinical application a manifold yet tough decision as it remains inconclusive which treatment can reap the greatest benefits.…”
Section: Discussionmentioning
confidence: 99%
“…One largesample meta-analysis described moxibustion can reduce gastrointestinal toxicities of radiotherapy (21). Despite several researches held discrepant attitudes towards different acupuncture therapies (22)(23)(24), an updated review could be feasible as researchers have gradually poured attention to this topic. Therefore, we hold the ambition for assessing the efficacy and safety of various acupuncture therapies for different RIAE by performing a Bayesian network metaanalysis (NMA).…”
Section: Introductionmentioning
confidence: 99%
“…16 Oncological palliative care recommendations. In a previous publication, we reported on the number of recommendations on the use of acupuncture in oncology, 81 while 788 BIRCH ET AL.…”
Section: Evidence For Acupuncture In Palliative Carementioning
confidence: 99%
“… 27 This has already been recommended in Clinical Practice Guideline through expert groups in oncology. 28 29 …”
Section: Introductionmentioning
confidence: 99%